31 Pulmonary hypertension in severe aortic stenosis: prevalence and reversibility with transcatheter aortic valve implant. (24th April 2016) - Rashid, S; Fox, J; Kapur, S; Kang, M; Schlosshan, D; Blackman, D; Malkin, C
Abstract : Introduction: We explored the impact of transcatheter aortic valve implantation (TAVI) on pulmonary hypertension (PH) by assessing the prevalence and reversibility of PH in an unselected TAVI cohort. We also identified factors that may predict PH and regression of PH after TAVI. Methods: Retrospective analysis of a local TAVI database. 308 consecutive patients underwent TAVI between 2008–13. Pulmonary artery systolic pressure (PASP) was estimated from the velocity of tricuspid regurgitation jet using Bernouille principle; PH was diagnosed if PASP was ≥50mmHg. Simple correlation (Spearman's rank rS) and regression analyses were used to determine predictors of PH and the change (and 95% confidence interval) in PASP (ΔPASP) after TAVI. Wilcoxon signed-rank Z-test was used to analyse ordinal data. Results: 71 (23%) patients had PH, in this group mean PASP before TAVI was 62 ± 6.5mmHg. PASP reduced in 56%, the mean ΔPASP was -12.8mmHg (95% C. I. -9.5 to -16.1, P < 0.001). PASP was weakly positively associated with the severity of MR (rS=0.276, p = 0.03); ΔPASP was associated only with baseline PASP (rS=0.3, p = 0.02) and change in LV end diastolic pressure (rS=0.4, p < 0.003). There were small improvements in severity of MR (Z=-3.5, p < 0.01) and a trend to improved LV function (Z=-1.9, p = 0.06) however regression analysis identified only change in LV end diastolic pressure to predict ΔPASP (p < 0.05). Conclusion: PH is common and usually reversible post TAVI. MR is a significant predictor of PH, the only predictor of regression of PH is reduction in LV end-diastolic function at implantation.